2020
DOI: 10.1093/jtm/taaa149
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic offers a key moment to reflect on travel medicine practice

Abstract: Highlight COVID-19 provides an opportunity to review travel health advice priorities. Infectious and non-infectious diseases are key for travel medicine, Research is warranted to stimulate an evidence-based balance in what travel medicine experts communicate to their clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Moreover, Phelan [ 9 ] outlined that COVID-19 vaccination, followed by immunity passports as a precondition for international travel, may cause discriminatory consequences if the World Health Organization does not revise its recommendations for the COVID-19 Public Health Emergency of International Concern in the International Health Regulations Annex 7. Accordingly, Hatz et al [ 10 ] concluded that the COVID-19 pandemic clearly demonstrates the importance of vaccinations for international travel, and potential travelers can expect to obtain country-specific requirements in the near future such as “immunity passports” and proof of vaccination. Lastly, in a recent interview with the World Travel and Tourism Council, CEO Gloria Guevara categorically stated that she is against COVID-19 vaccination as a precondition for international travel as such action could create discrimination [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Phelan [ 9 ] outlined that COVID-19 vaccination, followed by immunity passports as a precondition for international travel, may cause discriminatory consequences if the World Health Organization does not revise its recommendations for the COVID-19 Public Health Emergency of International Concern in the International Health Regulations Annex 7. Accordingly, Hatz et al [ 10 ] concluded that the COVID-19 pandemic clearly demonstrates the importance of vaccinations for international travel, and potential travelers can expect to obtain country-specific requirements in the near future such as “immunity passports” and proof of vaccination. Lastly, in a recent interview with the World Travel and Tourism Council, CEO Gloria Guevara categorically stated that she is against COVID-19 vaccination as a precondition for international travel as such action could create discrimination [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is to be expected that the pandemic will also influence the way Latin Americans prepare for future trips, as shown in the article "The COVID-19 pandemic offers a key moment to reflect on travel medicine practice", potential travelers will expect to receive detailed practical information on preventive and regulatory measures, travel restrictions and countryspecific requirements such as testing for protective antibodies, 'immunity passports' and later the proof of vaccination. 12 The pandemic taught many people that humans are also vectors, we can transport infectious agents from one country to another, a situation that depending on various factors can result in a global public health crisis like the one we are currently experiencing with the COVID-19. 13 Our results coincide with those published by Guerrero-Lillo et al, who showed that knowledge, attitudes, and practices about travel medicine in international travelers and medical students from Chile are deficient; 78.5% of the participants stated no knowledge of travel medicine, 6 here it was 73.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Many recommendations were developed to provide guidance on travel during the pandemic [ 2 , 3 , 4 ••, 5 , 6 , 7 •, 8 ••, 9 ]. Thoughtful reflections discussed the impact of the pandemic on travel and travel medicine, and many adaptations were made in response [ 4 ••, 10 12 , 13 •]. Given the resumption of travel, travel medicine providers and the travelling public should consider how this pandemic will influence the future of travel medicine.…”
Section: Introductionmentioning
confidence: 99%